Does an Avatar Motivate? - Mohammad Nur Azhar, Mazlan; Burd, Liz (IEEE, 2011)
The purpose of this study is to investigate students’ perceptionsof their motivation to learn while possessing an avatar along side the learning activities. The activities include attendance and accessing the course module’s eLearning portal.47students participated in the study and were divided into two groups:an avatar group and a non-avatar group. Additionally, two research instruments were used in the study. Firstly,an avatar environment named Avatar Hall was developed to allow the students from the avatar group to view their avatars.The second instrument was a motivation inventory, which was used to identify the students’ perceptions of the extent to which the presence of an avatar motivated them to learn. The results for both groups show a moderate percentage distribution of the students’ perceptions of their motivation to learn and further statistical test reveal no significant difference between the two groups of students in terms of their motivation to learn.